La competencia en la expresión oral de niños escolares en costa rica. el componente léxico - Araya Ramírez, Jéssica (2012)
In this article we analyze the lexical diversity in thirty-six schoolchildren from first to sixth grade at a public school in the regional directorate of san josé, circuit 10. the lexical wealth is valued from the diversity of words of content vocabulary which children use (nouns, adjectives and verbs), in textual productions in 50 set forth, calculated by the formula pd 50.